Narratology for teaching literature: a literature Review - Lopez Lluen, Jose Luis Geanpierre (2024)
The objective was to analyze the various contributions of narratology for the teaching of literature. The method used, within the framework of qualitative research, was the literature review. The results were oriented to three categories: the story in literary history, the story as a science: narratology, and narratology for the teaching of literature. The databases used were books linked to narrative theory, indexed journals, national and international theses repositories, and scientific articles. The search for information was oriented from the years of 1896 to the present, through a systematic, evolutionary and synchronous review. In the discussion, the approaches to literature from a theoretical and experiential reflection were detailed; the need to link narratology with Pedagogy was highlighted; and the limitations of the study were made known, above all, in the scarcity of research in Spanish. Three conclusions were reached: the narratology arises as a reflection of the story, in addition it should not be dissociated from the reality close to the student context; therefore, the focus of animation and mediation of literature from transversality should be highlighted to create literacy communities.